STRATEGY OF MADRASAH PRINCIPAL IN IMPLEMENTING MADRASAH PILOT PROJECT INTEGRITY ZONE TO IMPROVE TEACHER PERFORMANCE AND EDUCATIONAL SERVICES AT MAN 1 MUSI BANYUASIN - Mukti, Mukti; Zainuri, Ahmad; Handayani, Tutut (Jurnal Asy-Syukriyyah, 2025)
The implementation of the Integrity Zone Madrasah Pilot Project at MAN 1 Musi Banyuasin aims to improve teacher performance and educational services through strengthening the principles of integrity, transparency and accountability. This research explores the strategies applied by madrasa heads in implementing the project, as well as the factors that support and hinder its success. Using qualitative methods, data was collected through in-depth interviews and observations of madrasa heads, deputy heads of public relations, teachers and administrative staff. The research results show that the main strategies implemented include transparent resource management, objective evaluation of teacher performance, as well as providing rewards and coaching. Apart from that, a responsive complaints system and openness in decision making also supports the implementation of the Integrity Zone. Supporting factors for success include strong leadership, adequate human resource quality, government policy support, community participation, and an organizational culture that supports integrity. However, the challenges faced include limited human resources, inadequate infrastructure, and lack of support from local policy makers. In conclusion, the implementation of the Integrity Zone Madrasah Pilot Project at MAN 1 Musi Banyuasin was successful in improving teacher performance and the quality of educational services, however further monitoring and evaluation is needed to ensure the sustainability and effectiveness of the policies implemented.